Conceptual Analysis on the Way Brazilian Cities Work: A Macroscope View - Giannetti, Biagio F.; Agostinho, Feni; Almeida, Cecília M. V. B.; Sevegnani, Fábio (Frontiers in Sustainable Cities, 2020)
Cities play a crucial role in the development of nations, since they are responsible to concentrate energy from diverse forms and transform it into higher quality outputs. An alternative way in assessing urban agglomerates is by means of Odum’s macroscope, represented by the eMergy synthesis method, which allows understanding and quantifying the energy flows driving cities functioning. The macroscope is able to identify the relationship of dependence among cities and their surrounding environment that provides less concentrated resources to be transformed into high quality products and information, as well as undesired by-products. After two decades developing studies related to urban systems and the Odum’s macroscope, the research team of Paulista University in Brazil acquired experience and maturity to write this conceptual analysis about how Brazilian cities work. Several cases are provided (including anabolic and catabolic ones) to sustain final insights towards more sustainable cities in Brazil. The main identified characteristics about how Brazilian cities work, derived from the case studies presented, can be summarized as: (i) the growing importance of studies focused on cities including their surrounding supporting areas to assess their sustainability; (ii) the need for both macro and micro perspectives when assessing cities’ sustainability; (iii) the importance in using Odum’s macroscope for a holistic understanding of cities’ sustainability performance; (iv) the importance in using Odum’s macroscope to understand how to achieve higher quality of life; (v) the use of macro and micro perspectives in supporting public-oriented policies.